Gender differences in drug abuse in the forensic toxicological approach. (August 2016) - Buccelli, C.; Della Casa, E.; Paternoster, M.; Niola, M.; Pieri, M.
Highlights: Gender differences in use/abuse of psychoactive and psychotic drugs are discussed. Differences may be due to both sociocultural factors and biological differences. A crucial role played by ovarian hormones has been evidenced for stimulants. Gender can influence the experienced effects to the same drug intake. Gender may affect the relationship between drug absorption and intoxication. Abstract: Gender differences in substance use/abuse have been the focus of research in the last 15 years. Initiation, use patterns, acceleration of disease course, and help-seeking patterns are known to be influenced by gender differences with regard to biological, psychological, cultural and socioeconomic factors. This paper presents a systematic review of published data on gender differences in the use/abuse of psychoactive and psychotic drugs, focusing on the importance of a multidisciplinary approach. The basis for this paper was obtained by Medline searches using the search terms "human" and "gender", combined with individual drug names or "drugs of abuse". The reference lists of these papers were further checked for other relevant studies. The gender difference in drug abuse is more evident in adults than in adolescents (13–19 years): adult men are 2–3 times more likely than women to develop drug abuse/dependence disorders and approximately 4 times as likely to have an alcohol use disorder. Such prevalence rates have not been observed in adolescents. Differences between men and women involve: (i) the biological response to the drug, (ii) the progression to drug dependence, and (iii) the comorbid psychiatric diagnoses, which may be due to both sociocultural factors and innate biological differences. A crucial role played by ovarian hormones (oestrogens and progesterone) has been documented in both human and animal model studies. Epidemiological data on how particular psychobiological and physiological characteristics in females influence vulnerability to both drug addiction and toxicological consequences of drugs are still in their infancy. Significant gaps remain in our knowledge, which are primarily attributable to the lack of empirical data that only a systematic and multidisciplinary approach to the topic can generate. The introduction of gender into forensic toxicological evaluations may help elucidate the relationship between the body's absorption of abused drugs (alone or in combination) and the onset of intoxications, both lethal and none.